Religion, Conflict, and Peacemaking: An Interdisciplinary Conversation - Schmid, Muriel (University of Utah Press, 2017)
Intro -- Contents -- Foreword by Thomas N. Maloney -- Acknowledgments -- 1. Religion's Long Shadow: A Brief Overview of the Conversation, Muriel Schmid -- Part 1. Religions in Dialogue -- 2. Interfaith Dialogue and Religious Leaders in the Israeli-Palestinian Context: Needs and Limitations, Mohammed Abu-Nimer -- 3. The Use of Dialogue in Transforming Religious Conflict, David Derezotes -- Part 2. Religious Identity and American Perspectives -- 4. The American Way of Religion and Violence?, John D. Carlson -- 5. Confronting Historic Injustice, Elaine Enns and Ched Myers -- Part 3. Religion and the Defense of Human Rights -- 6. From Amnesty International to Right to Nonviolence: Theory and Practice in the Arab Spring Context, Chibli Mallat -- 7. Partnering in Nonviolent Resistance: The Evolution of Christian Peacemaker Teams, Kathleen Kern and Tim Nafziger -- Part 4. Christian and Muslim Discussions -- 8. John Paul II and the "Just War" Doctrine: "Make Peace through Justice and Forgiveness, Not War", James L. Heft -- 9. Peace, Conflict, and Conflict Transformation in the Islamic Tradition, Abbas Aroua -- 10. In the Beginning Was Conflict: Creation, John Paul Lederach -- Part 5. Religion and Personal Conflict -- 11. Contact, Connection, and Community: Religion and Peacemaking, Laura M. Bennett-Murphy -- Bibliography -- List of Contributors -- Index